2014
DOI: 10.1111/imj.12335
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of beds on the general medical unit by ‘non‐acute medical’ patients: a retrospective study of incidence and cost in two Tasmanian regional medical hospital units

Abstract: The incidence of non-acute medical admissions and non-acute medical bed days to the medical unit and associated cost was significant. Further research is needed to design alternative care provision for such patients particularly in regional Australia. The potential savings to the Australian healthcare system could be significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…At least 4 studies referred to the cost of inappropriate admissions for specific health conditions of surgical procedures …”
Section: Resultsmentioning
confidence: 99%
“…At least 4 studies referred to the cost of inappropriate admissions for specific health conditions of surgical procedures …”
Section: Resultsmentioning
confidence: 99%
“…Improving hospital patient flow is important in order to optimise the use of limited healthcare resources efficiently, 1 minimise iatrogenic adverse events, 2 and it may ensure patient-centred care. 3,4 Numerous studies have identified problems with patient flow in the emergency department, [5][6][7] acute care 8,9 and rehabilitation hospitals. 10,11 Barriers to discharge from hospital are common, with reports that these occur in approximately 14-16% of acute hospital 12,13 and rehabilitation admissions.…”
Section: Introductionmentioning
confidence: 99%
“…Около 2 млн американцев ежегодно переносят НИ, от которых, согласно Центру контроля и профилактики болезней, ежегодно умирает 90 000, причем наблюдается тенденция к росту показателей летальности. Если принять во внимание, что в конце ХХ века в США каждый год необоснованно госпитализировалось 8,9 млн человек [4], а НИ переносили ежегодно около 2 млн американцев [5], то, по простым подсчетам, оказывается, что более чем каждый четвертый пациент, госпитализированный без показаний, становился мишенью НИ, т.е. жертвой госпитальных ятрогений.…”
Section: ãîñïèòàëüíûå ÿòðîãåíèèunclassified